Comparison of Phenylephrine and Ephedrine in Treatment of Spinal-Induced Hypotension in High-Risk Pregnancies: A Narrative Review - Dusitkasem, Sasima; Herndon, Blair H.; Somjit, Monsicha; Stahl, David L.; Bitticker, Emily; Coffman, John C. (Frontiers in Medicine, 2017)
Purpose: To compare maternal and fetal effects of intravenous phenylephrine and ephedrine administration during spinal anesthesia for Cesarean delivery in high-risk pregnancies. Source: An extensive literature search was conducted using the US National Library of Medicine, MEDLINE search engine, Cochrane review and Google Scholar using search terms “ephedrine and phenylephrine” /or “preterm and term and spinal hypotension” /or “preeclampsia and healthy parturients” /or “multiple and singleton gestation and vasopressor”. Society of Obstetric Anesthesia and Perinatology meeting abstracts for the past 4 years were also searched for relevant studies. Principle findings: Both phenylephrine and ephedrine can safely be used to counteract hypotension after spinal anesthesia in patients with uteroplacental insufficiency, pregnancy-induced hypertension and in non-elective Cesarean deliveries. Vasopressor requirements before delivery in high risk Cesarean sections are reduced compared to healthy parturients. Among the articles reviewed, there were no statistically significant differences in umbilical arterial pH, umbilical venous pH, incidence of fetal acidosis, Apgar scores, or maternal hypotension when comparing maternal phenylephrine and ephedrine use. Conclusion: From the limited existing data, phenylephrine and ephedrine are both appropriate selections for treating or preventing hypotension induced by neuraxial blockade in high risk pregnancies. There is no clear evidence that either medication is more effective at maintaining maternal blood pressure or has a superior safety profile in this setting. Further investigations are required to determine the efficacy, ideal dosing regimens and overall safety of phenylephrine and ephedrine administration in high-risk obstetric patients, especially in the presence uteroplacental insufficiency.